IFRS adoption and economic growth in developing economies - Owusu, Godfred Matthew Yaw; Suppiah, Susela Devi K.; Mohd Saat, Nur Ashikin; Law, Siong Hook (Inderscience Publishers, 2021)
We examine whether the adoption of International Financial Reporting Standards (IFRS) affects economic growth in developing economies and investigate the role that country-level institutional quality plays in the relationship. Using a panel data averaged over three non-overlapping years, from the period 1996 to 2013, for 78 developing countries and employing the efficient two-step system generalised methods of moment (GMM) estimation technique; we find that countries that adopt IFRS experience better economic growth than non-adopting countries. Our results also demonstrate that good institutions moderate the IFRS-economic growth nexus. Taken together, these findings suggest that IFRS adoption has important implications for economic growth.